Tata Laksana Pengelolaan Keuangan Masjid Nur Al-Iman Kabupaten Musi Rawas - Hanif, Padlim; Amelia, Ivana; Farhan, Muhammad (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2021)
The management of mosque finances is one of the most important parts of mosque governance, therefore its management should be a concern so that the realization of budgeted funding can benefit the wider community. This is because a mosque that is prosperous and rahmatan lil alamin is what can create changes in life for the better, not only for the congregation but also for many other people. This research was conducted at the Nur Al-Iman Mosque in Musi Rawas Regency, South Sumatra Province with the main focus being to find out the management of mosque finances carried out by the mosque's administrators. The approach used in this research is qualitative research. The results of this study indicate that the concept of transparency has been used by the takmir of the Nur Al-Iman Musi Rawas Mosque through the separation of the allocation of funds by separating the infaq box. In addition, the mosque takmir has also used the concept of accountability. The embodiment of the concept of accountability is applied by the manager or takmir of the Nur Al-Iman Mosque, Musi Rawas Regency, both for the financial and non-financial dimensions, all of which are disclosed in reports regularly and in real-time for a certain period, namely weekly, monthly, and yearly.